Age-friendly cities and communities and cognitive health among Chinese older adults: Evidence from the China Health and Retirement Longitudinal Studies. (January 2023) - Shi, Jiaming; Liu, Xiaoting; Feng, Zhixin
Abstract: The idea of the environment as a determinant of cognitive health for older adults has been widely accepted. The concept of the "Ageing-Friendly City and Community" (AFCC), which emphasises the importance of both social environment (SE) and built environment (BE) and encompasses environments at both community and city levels, has been proposed by the World Health Organization, to improve older adults' wellbeing. Using data from the China Health and Retirement Longitudinal Studies, this study explored the effects of the AFCC at both community and city levels on older adults' cognitive health. It also investigated the effects of the AFCC on two special domains of cognitive health: mental intactness and episodic memory. Multilevel regression models were applied. The results show that SE with better community support and social participation, and BE with a higher level of community safety and better housing and transportation at a community level, were both significantly associated with better cognitive health. Meanwhile, an AFCC at a city level was not significantly associated with cognitive health. Older adults' social activities and depression symptoms were mediators to explain the effects of the AFCC on their cognitive health. An AFCC significantly moderated the effects of social activities and depression symptoms on episodic memory, but no significant moderating effects were found for mental intactness. Highlights: Better community support and social participation were significantly associated with better cognitive health. A higher level of community safety and better housing and transportation were significantly associated with better cognitive health. Psychological mechanism and behavioural mechanism have been found to be explained the associations between AFCC and cognitive health.